Potential tourist assets in Georgia - Pirveli, Marika (Turyzm/Tourism, 2000)
The author is mainly interested in selected geographical, natural, socio-cultural and historical assets of Georgia, which are potential future tourist assets of the region. Georgia, similarly to Armenia and Azerbaijan, as well as all the other administrative units within the Caucasian region, is an organic and inseparable part of Caucasia. Therefore, however the article discusses the tourist potential of Georgia, it also contains information about and references to the whole region. Placing Georgia in the geographical, historical, cultural and mental space, as well as giving several basic statistical parameters referring to its area and population, introduce the reader to the exotic and not well known area, presenting it against the whole region. Most often it is the Caucasian Region, less frequently - the Mediterranean Region. The next part of the text touches upon the Georgian religious belief, language and alphabet - through historical facts the author follows their development. The socio-cultural, historical and natural assets constitute the main part of the article. Since these assets are discussed with a potential tourist in mind, the mentality of the Caucasian population is also briefly presented. Further the author describes the tourist infrastructure and the transportation accessibility. A table can be found, where there is information about selected transport connections and accommodation outlets, as well as the evaluation of seasonality, which proves the all-year-round attractiveness of Georgia.